Disseminated intravascular coagulation in obstetrics: Etiopathogenesis and up to date management strategies [Obstetri̇de yaygin damari̇çi̇ koagülasyon: Etyopatogenez ve güncel tedavi̇ strateji̇leri̇] - (:unkn) unknown (My University, 2014)
Disseminated intravascular coagulation related to obstetric conditions is rarely seen but is associated with high morbidity and mortality. Recently, pathophysiology of disseminated intravascular coagulation has not been understood well and, therefore, effective and permanent treatment strategies are missing. In this review, we try to discuss the etiology, current diagnostic approaches and management strategies of disseminated intravascular coagulation from the perspectives of clinicians.
Keywords: Disseminated intravascular coagulation; Morbidity and mortality; Pregnancy